A Quality systems study on Labtech Manufacturing industries, Inc. - Castillo, Kermin Amor T. (College of Engineering, 1996)
Labtech Manufacturing Industries is a contract manufacturer of silicon diodes and transistors for Shindengen Electronics Japan. An evaluation of its quality system was conducted wherein the product D3SBA was used as a spring board for the evaluation and discussion of its quality systems and procedures There is awareness of quality in the departments concerned with production. Systems and procedures for quality such as statistical process control are already being implemented. Specific quality objectives are set and targeted for production. However, the following problem areas have been found in LMI: 1.The tools used for statistical process control are insufficient. 2. No process capability studies are carried out. 3.Procedures and organization for quality are not completely documented; 4. Quality cost information is not completely utilized; 5. The company lacks a quality policy or an integrated quality program; 6.The management of LMI lacks commitment to quality and long-term growth. The makers of this study have the following recommendations: 1. Implement a complete Statistical Process Control (SPC) Program. 2. Document completely procedures and organization for quality; 3. Set up a system that will compute and utilize quality costs; 4. Introduce and implement a Total Quality Management (TQM) Program.